Crystal structure of ethyl 4-methyl-2-oxo-5-phenyl-1,3,4-oxadiazinane-3-carboxylate, C13H16N2O4 - Caracelli, Ignez; Zukerman-Schpector, Julio; Rodrigues, Alessandro; Vinhato, Elisângelo; Olivato, Paulo R.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C13H16N2O4, orthorhombic, P212121 (no. 19), a = 6.7876(2) Å, b = 8.8984(2) Å, c = 22.3399(6) Å, V = 1349.30(6) Å3, Z = 4, Rgt(F) = 0.0384, wRref(F2) = 0.0947, T = 293(2) K.